PELAKSANAAN PENCATATAN DAN PELAPORAN PIS-PK DI PUSKESMAS - Amalia, Dewi; Sugiarti, Ida (Jurnal Informasi Kesehatan Indonesia (JIKI), 2023)
Background: With the support of the Indonesian Healthy Program with a Family Approach (PIS-PK), the Ministry of Health of the Republic of Indonesia supports the Healthy Living Society Movement (GERMAS). In terms of changing the pain paradigm into a healthy paradigm for improving standards of health, the PIS-PK program is relevant to the purposes of Indonesia's Healthy Mission. Subjects and Method: Phenomenological methods are used in qualitative research. Puskesmas Ciawi created the study's location. Five important, important, and important informants participated in the research, that was done in February 2023. One PIS-PK coordinator of Puskesmas, a head for Puskesmas, a data input officer of Puskesmas, and a responsible PUS-PK of the Ministry of Health consisted of the informants. The aim of this research is to find out how the implementation of recording and reporting PIS-PK in Puskesmas Ciawi with a phenomenological approach. Results: In Puskesmas Ciawi in 2018 and 2019, the Regulation of the Minister of Health No. 39 of 2016 on Guidelines for the Maintenance of the Indonesian Healthy Program with Family Approach (PIS-PK) came as a result. In Puskesmas is Ciawi, PIS-PK has been recorded manually and electronically. Reports are made once a month, and statements are submitted on the Family Health Profile (Prokesga) form. However, additional factors make its implementation less effective. The incapacity to quickly connect to the internet is one, as is a lack of facilities. Conclusion: In Puskesmas Ciawi, the PIS-PK reporting and reporting is quite good. However, the central government still must give more attention to the region for the Indonesian Healthy Program with a Family Approach if it is a success.